RESEARCH-AND-PRODUCTION ASSOCIATION: SPECIFICITY OF EFFECTS OF INTEGRATION - A. Voit (Вестник университета)
The aim of the work is the formalization of the basic directions of manifestations of effects from the integration of high-tech enterprises in the research-and-production association. In the article the urgency of integration within the framework of the strategic development of the enterprises of knowledge-based industries, disclosed the prerequisites and specificities of the integration processes in modern Russia. Explored approaches to key areas of integration cubed. Specificity of research-and-production association, which causes a variety of manifestations of the effects of integration. The author's approach is proposed to formalize the effects from the integration for new research-and-production association, consisting of control units, ensuring the development and implementation of activities.